Relationships between waist-to-hip circumference ratio and gender, age and nutritional status in Thai children in Mueang District, Chiang Mai Province - Pruenglampoo, Sakda; Taejaroenkul, Sineenart; Sirisanthana, Virat (Biomedical Sciences and Clinical Medicine, 2024)
Objectives To investigate the relationship between waist-hip circumference ratio (WHR) and demographic factors including gender, age and nutritional status and construct standard reference tables of WHR in Thai children and adolescents. Methods This cross sectional study was carried out during 2001-2002 in Mueang district, Chiang Mai province, northern Thailand. The participants comprised 2,537 children (1,215 boys and 1,322 girls) aged between 6 and 15 years, who were selected randomly from public (n=13) and private (n=9) schools. Their weight, height, and waist and hip circumferences were measured. The nutritional status was categorized into 4 groups: under-nourished, normal, overweight and obese. The relationship between WHR and demographic factors was investigated by using ANOVA. Results The standard reference tables of WHR were constructed to categorize 2,537 Thai children and adolescents by gender, age and nutritional status. The mean and standard deviation of WHR for all participants was 0.81±0.06. The WHR in the participants included associated factors such as gender, age and nutritional status, which were significantly smaller in girls than boys. WHR also decreased with age. Nutritional status was categorized into 4 groups, with all mean WHR having a statistically significant difference from one another. The under-nourished group had the lowest WHR, whereas the obesity group had the highest. Conclusion This is the fi rst study that provides tables of WHR by gender, age, and nutritional status in Thai children and adolescents. They show the standard for a subsequent surveillance study as well as research of abnormal body form in these participants.